Microeconomic Models of Overlapping Competing Jurisdictions (FOCJs) - Chebotareva, Mariia; Friedrich, Peter (Estonian Discussions on Economic Policy, 2017)
One of the newer suggestions for the design of public economic units refers to Functional Overlapping Competing Jurisdictions (FOCJs), which are instruments to shape cooperation of jurisdictions, e.g. municipalities. The study clarifies important types of FOCJ. It concentrates on FOCJs where the members are municipalities. How useful such FOCJs are for designing public services depends on the composition of members, their decision concept of cooperation, the task of the FOCJ, the resources devoted to the FOCJ and the development phase of the FOCJ. For better understanding of those determinants, a microeconomic theory is needed. Therefore, the authors formulate models of FOCJ establishment, FOCJ operation and FOCJ competition for clients and members. The authors present already existing models and extensions of them based on the models in public choice and location theory, cooperation and game theory, and market theory to cover oligopolistic situations.